Social and cognitive congruence [data]: tutees and tutor's agreement on social and cognitive congruence in a sonography peer-assisted learning scenario - Dönnhoff, Ivo (Universität, 2022)
This dataset contains the R-Script of our Evaluation and the dataset on which our results are based.